INCOME TAX PAID BY ENTERPRISES AND ITS FEATURES - Zaripov Husan Bakhodirovich (European Science Publishing, 2024)
This article examines the reforms carried out in relation to the income tax paid by enterprises operating in our country and their results. It also describes the calculation of advance payments for income tax, existing problems and ways to solve them. Based on the results of the study, conclusions were formed and scientific proposals and practical recommendations were developed. Of particular importance in improving the tax system is the improvement of the administration of income tax. Because although income tax is the main tax that generates budget revenues, it is also an effective means of ensuring the competitiveness of the country's economy. The income tax has a positive impact on improving the competitiveness of the national economy, based on stimulating foreign direct investment, exports and certain sectors of the economy due to the low tax rate.
Keywords: tax, tax concept, profit, income tax, taxpayers, tax rate, advance payment.